DEFINITIVE ANALYSIS OF BASIC PEDAGOGICAL CONCEPTS OF PROFESSIONAL ACTIVITIES OF FUTURE FITNESS TRAINERS - Катерина Максимова; Ірина Соіна; Ніна Петрусенко (Institute of Pedagogy of NAES, 2024)
The article analyzes and summarizes the definitive analysis of the basic concepts of the professional activity of future fitness trainers, which are the subject of research into the problem of professional training of future fitness trainers in institutions of higher education in today's conditions. The essence of such concepts as: "fitness", "trainer", "fitness trainer", "future fitness trainer", "professional competence of future fitness trainers, which is formed in institutions of higher education", "professional training of future fitness trainers in institutions of higher education". The concept of "fitness" is revealed as a system of socio-economic, cognitive and human-creating objects and processes that reflect the unity of system-structural and value-pragmatic aspects of a healthy lifestyle, as well as a socio-cultural mechanism of reproduction of human existential forces, which is realized in the process of personally oriented broadcasting culture, social and professional experience in society. The factors that determine the approach to considering fitness as a sociocultural phenomenon, which are solved with the help of fitness, are established, namely: socialization of people engaged in fitness, provision of ample opportunities for self-knowledge; self-identification and self-actualization of the individual and its most favorable interactions with society; promoting the emergence of new cultural forms through the creative activity of people in the field of fitness; attracting people to the cultural values ​​of different countries and peoples in the process of fitness classes; development of the fitness industry and the network of paid fitness services based on various types of state institutions; setting a precedent for scientific research in the field of fitness, which contributes to the development of science; creation of grounds for the development of a training system for fitness specialists, the need to develop new professional educational programs. The concept of "professional competence of a future fitness trainer" is defined as "an integrative characteristic of an individual, determined by the level of mastery of fundamental knowledge of fitness. The concept of "professional training of future fitness trainers in institutions of higher education" is analyzed as a pedagogical system aimed specifically at the formation of their professional competence nowadays.